Synthesis of 4-substituted azopyridine-functionalized Ni(II)-porphyrins as molecular spin switches - Ludwig, Jannis; Moje, Tobias; Röhricht, Fynn; Herges, Rainer (Beilstein Journal of Organic Chemistry, 2020)
We present the synthesis and the spin switching efficiencies of Ni(II)-porphyrins substituted with azopyridines as covalently attached photoswitchable ligands. The molecules are designed in such a way that the azopyridines coordinate to the Ni ion if the azo unit is in cis configuration. For steric reasons no intramolecular coordination is possible if the azopyridine unit adopts the trans configuration. Photoisomerization of the azo unit between cis and trans is achieved upon irradiation with 505 nm (trans→cis) and 435 nm (cis→trans). Concurrently with the isomerization and coordination/decoordination, the spin state of the Ni ion switches between singlet (low-spin) and triplet (high-spin). Previous studies have shown that the spin switching efficiency is strongly dependent on the solvent and on the substituent at the 4-position of the pyridine unit. We now introduced thiol, disulfide, thioethers, nitrile and carboxylic acid groups and investigated their spin switching efficiency.
Keywords: azopyridines; Ni(II)-porphyrins; photoswitch; record player molecules; spin state; spin switch

(untitled) - Venkataramani, S.; Jana, U.; Dommaschk, M.; Sönnichsen, F. D.; Tuczek, F.; Herges, R. (Science, 2011)

(untitled) - Matino, F.; Schull, G.; Jana, U.; Köhler, F.; Berndt, R.; Herges, R. (Chem. Commun., 2010)

(untitled) - Dommaschk, M.; Gröbner, J.; Wellm, V.; Hövener, J.-B.; Riedel, C.; Herges, R. (Phys. Chem. Chem. Phys., 2019)

(untitled) - Dommaschk, M.; Peters, M.; Gutzeit, F.; Schütt, C.; Näther, C.; Sönnichsen, F. D.; Tiwari, S.; Riedel, C.; Boretius, S.; Herges, R. (J. Am. Chem. Soc., 2015)

(untitled) - Heitmann, G.; Schütt, C.; Gröbner, J.; Huber, L.; Herges, R. (Dalton Trans., 2016)

German Patent - Herges, R.; Dommaschk, M.; Heitmann, G.; Groebner, J.; Thoms, V. (Neuartiges MRT-Kontrastmittel, Verwendung zur Temperaturmessung und Verfahren zur Temperaturmessung, 2019)

WO Patent - Herges, R.; Dommaschk, M.; Heitmann, G.; Groebner, J.; Thoms, V. (Neuartiges mrt-kontrastmittel, verwendung zur temperaturmessung und verfahren zur temperaturmessung, 2009)

(untitled) - Stadler, E.; Tassoti, S.; Lentes, P.; Herges, R.; Glasnov, T.; Zangger, K.; Gescheidt, G. (Anal. Chem. (Washington, DC, U. S.), 2019)

(untitled) - Stadler, E.; Dommaschk, M.; Frühwirt, P.; Herges, R.; Gescheidt, G. (ChemPhysChem, 2018)

(untitled) - Wagner, G. E.; Tassoti, S.; Glanzer, S.; Stadler, E.; Herges, R.; Gescheidt, G.; Zangger, K. (Chem. Commun., 2019)

(untitled) - Köbke, A.; Gutzeit, F.; Röhricht, F.; Schlimm, A.; Grunwald, J.; Tuczek, F.; Studniarek, M.; Longo, D.; Choueikani, F.; Otero, E.; Ohresser, P.; Rohlf, S.; et al. (Nat. Nanotechnol., 2020)

(untitled) - Thies, S.; Bornholdt, C.; Köhler, F.; Sönnichsen, F. D.; Näther, C.; Tuczek, F.; Herges, R. (Chem. – Eur. J., 2010)

(untitled) - Gutzeit, F.; Dommaschk, M.; Levin, N.; Buchholz, A.; Schaub, E.; Plass, W.; Näther, C.; Herges, R. (Inorg. Chem., 2019)

(untitled) - Ludwig, J.; Gröbner, J.; Dommaschk, M.; Huber, L. M.; Peters, M. K.; Hövener, J.-B.; Herges, R. (J. Porphyrins Phthalocyanines, 2020)

(untitled) - Heitmann, G.; Dommaschk, M.; Löw, R.; Herges, R. (Org. Lett., 2016)

(untitled) - Lindsey, J. S.; Schreiman, I. C.; Hsu, H. C.; Kearney, P. C.; Marguerettaz, A. M. (J. Org. Chem., 1987)

(untitled) - Lindsey, J. S.; Wagner, R. W. (J. Org. Chem., 1989)

(untitled) - Baeyer, A. (Ber. Dtsch. Chem. Ges., 1874)

(untitled) - Reuter, R.; Wegner, H. A. (Chem. – Eur. J., 2011)

(untitled) - Yasukawa, N.; Kuwata, M.; Imai, T.; Monguchi, Y.; Sajiki, H.; Sawama, Y. (Green Chem., 2018)

(untitled) - Purkait, A.; Roy, S. K.; Srivastava, H. K.; Jana, C. K. (Org. Lett., 2017)

(untitled) - Zagulyaeva, A. A.; Banek, C. T.; Yusubov, M. S.; Zhdankin, V. V. (Org. Lett., 2010)

(untitled) - Yusubov, M. S.; Zagulyaeva, A. A.; Zhdankin, V. V. (Chem. – Eur. J., 2009)

(untitled) - Zagulyaeva, A. A.; Yusubov, M. S.; Zhdankin, V. V. (J. Org. Chem., 2010)

(untitled) - Yoshimura, A.; Neu, H. M.; Nemykin, V. N.; Zhdankin, V. V. (Adv. Synth. Catal., 2010)

(untitled) - Yusubov, M. S.; Nemykin, V. N.; Zhdankin, V. V. (Tetrahedron, 2010)

(untitled) - Fletcher, D. A.; Gowenlock, B. G.; Orrell, K. G. (J. Chem. Soc., Perkin Trans. 2, 1997)

(untitled) - Taher, D.; Wallbank, A. I.; Turner, E. A.; Cuthbert, H. L.; Corrigan, J. F. (Eur. J. Inorg. Chem., 2006)

(untitled) - Dunn, A. D.; Norrie, R.; L'Hostis, J.; Marjot, S. (J. Prakt. Chem., 1992)

(untitled) - Kreis, M.; Bräse, S. (Adv. Synth. Catal., 2005)

(untitled) - Sato, C.; Suzuki, S.; Kozaki, M.; Okada, K. (Org. Lett., 2016)

(untitled) - Nasri, N. S.; Jones, J. M.; Dupont, V. A.; Williams, A. (Energy Fuels, 1998)

(untitled) - Rodriguez, J. A.; Hrbek, J. (Acc. Chem. Res., 1999)

(untitled) - Nishimura, O.; Kitada, C.; Fujino, M. (Chem. Pharm. Bull., 1978)

(untitled) - Dommaschk, M.; Schütt, C.; Venkataramani, S.; Jana, U.; Näther, C.; Sönnichsen, F. D.; Herges, R. (Dalton Trans., 2014)

(untitled) - Hansch, C.; Leo, A.; Taft, R. W. (Chem. Rev., 1991)